San Josemaría Escrivá de Balaguer, “Palabras del Nuevo testamento, repetidas veces meditadas. Junio – 1933” / Saint Josemaría Escrivá, “Frequently Meditated Words from the New Testament. June – 1933” - Francisco Varo (Studia et Documenta)
Eight-page document, handwritten by Saint Josemaría and headed with the inscription: “Frequently meditated words from the New Testament. June – 1933”. Contains a list of 112 texts from the New Testament with occasional short explanatory notes added. This study presents the commented transcription of the handwritten document, preceded by an introduction which includes: a description of the manuscript, some notes about the historical context in which it was written, some suggestions as to how, possibly, it was redacted, and an initial reflection on its contents.